Influence of nanoencapsulation and freeze-drying on the antioxidant capacity of a carotenoid-rich extract from pumpkin - Nicola Pinna; Francesca Blasi; Maurizio Ricci; Aurélie Schoubben (Applied Food Research)
The purpose of the work was to develop carotenoid-loaded nanostructured lipid carriers (NLCs) that were freeze-dried with trehalose to enhance formulation stability. These bioactive compounds possess significant role in human health, acting as powerful antioxidants and offering benefits for vision, skin health, and immune function. However, carotenoids present challenges due to their poor stability. Carotenoids were first extracted from pumpkin using ultrasound-assisted extraction method. The oil for the NLC production was extracted from pumpkin seeds using a Soxhlet extractor. NLCs were produced using high-pressure homogenization and characterized for their size using photon correlation spectroscopy, extract recovery, content and encapsulation efficiency using UV–Vis spectrophotometry. The NLC thermal behavior was evaluated using differential scanning calorimetry and their antioxidant capacity using the ABTS assay. The qualitative and quantitative carotenoid profiles were determined using HPLC-DAD, while carotenoid identification was carried out using UHPLC-DAD coupled to a quadrupole-time-of-flight mass spectrometer. NLCs (5 and 10 % theoretical loading) were characterized by suitable dimensions (∼230 nm) for oral administration and high extract recovery (91–93 %). The extract contents were of 4.1 and 8.5 % for 5 and 10 % CE-NLCs, respectively, corresponding to 88–94 % encapsulation efficiencies. Thermal analysis revealed a shift in the solid lipid melting due to the oil incorporated into the nanoparticles. Freeze-drying with 10 % (w/v) trehalose combined with a 1:10 sample dilution effectively preserved NLC dimensions (∼270 nm). The antioxidant capacity and the qualitative-quantitative composition of the extract were preserved following nanoencapsulation and freeze-drying. The new formulation exhibits optimal features for application in functional foods and nutraceuticals.